2015
DOI: 10.1007/s11136-015-1172-7
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative and bidirectional association of physical activity and sedentary behaviour with health-related quality of life in adolescents

Abstract: The association between PA and HRQoL was cumulative and bidirectional among adolescents, whereas low HRQoL seemed to be a consequence of high SB rather than a cause (cumulative but not bidirectional). Promoting recommended PA and low SB may help improve HRQoL among adolescents, with a possible virtuous cycle with regard to PA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
55
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 33 publications
4
55
0
2
Order By: Relevance
“…However, low HRQoL appeared to be a consequence (rather than driver) of a sedentary lifestyle, suggesting the high complexity in these associations. 12 Nonetheless, our results did suggest that physical activity was important to HRQoL, because potterers who spent little time in physical activity had the lowest HRQoL scores.…”
Section: Figurementioning
confidence: 53%
See 2 more Smart Citations
“…However, low HRQoL appeared to be a consequence (rather than driver) of a sedentary lifestyle, suggesting the high complexity in these associations. 12 Nonetheless, our results did suggest that physical activity was important to HRQoL, because potterers who spent little time in physical activity had the lowest HRQoL scores.…”
Section: Figurementioning
confidence: 53%
“…Their "unstructured recreation" group had the worst perceptions of school environment, academic performance, and levels of truancy across the 5 clusters identified, whereas their "study" cluster showed the best well-being and functioning. In the variable-centered studies, more frequent physical activity, 12 less screen time, 13 and adequate or more sleep 14, 15 in isolation were associated with marginally better HRQoL.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Of the 13 studies, 11 examined screen time alone (22,23,34,39,41,46,47,(49)(50)(51)(52), one examined reading and music listening on top of screen time (38), and one examined overall sedentary behaviour (duration of sitting) (44). Of the 13 studies, 11 examined screen time alone (22,23,34,39,41,46,47,(49)(50)(51)(52), one examined reading and music listening on top of screen time (38), and one examined overall sedentary behaviour (duration of sitting) (44).…”
Section: Relationships Between Hrql and Variable-centred Time Usementioning
confidence: 99%
“…Physical activity and HRQL were investigated in 15 studies (11 cross-sectional, four longitudinal), perhaps reflecting the global obesity epidemic (40). All used stylised questions to estimate frequency and/or duration time in physical activity; most used previously reported questions (23,34,35,37,38,(41)(42)(43)(44)(45)(46)(47), while the remainder used studydesigned measures (22,36,37,48). Many physical activity measures comprised one to three items.…”
Section: Relationships Between Hrql and Variable-centred Time Usementioning
confidence: 99%